A note on the residual term R in the decomposition of the Gini index - Monti, Maria (Uniwersytet Ekonomiczny we Wrocławiu, 2008)
In this paper we reconsider the Dagum decomposition of the Gini index and we compare this decomposition with the decompositions proposed by Mookherjee and Shorrock and by Lambert and Aronson. In so doing, a deeper insight into the meaning of the overlapping term is given and an alternative expression for this term is obtained. The results are applied to a sub-sample of the C.S.O. survey: the families taken into consideration are selected and grouped according to the number of their components. The aim is to analyze how the present Polish personal income tax modifies the overall income distribution and to evaluate the changes in the within and between groups income inequalities
Argumenta Oeconomica, 2008, No 1 (20), s. 107-138
Keywords: Gini coefficient; inequality decomposition; Gini residual